Low performance of sinovac vaccine particularly with belatacept therapy in a study with different types of COVID-19 vaccines in transplanted patients (2023)
The huge impact of SARS-CoV-2 infections on organ transplant recipients makes it necessary to optimize vaccine efficacy in this population. To effectively implement multiple strategies, it is crucial to understand the performance of each type of available vaccine. In our study, the antibody titer was measured, and the presence of antibodies against SARS-CoV-2 was evaluated after 90 days of immunization; furthermore, the differences between hybrid immunity, immunity by vaccination, and immunosuppressant type were identified. As a result, of the patients included in this study (n = 160), 53% showed antibodies against SARS-CoV-2 90 days after the first dose in patients who had completed the vaccination schedule. Antibody titers were higher in patients with hybrid immunity, and the proportion of nonresponsive patients was higher among those who received the immunosuppressant belatacept in their post-transplant regimen (P = .01). Only 15% of patients treated with this medicine seroconverted and patients vaccinated with Corona- Vac and treated with belatacept showed no response. In conclusion, a reduced response to vaccines against SARS-CoV-2 was identified in the transplant population, and this response varied with the type of vaccine administered and the immunosuppressive treatment.